The Impact of Academic Press and Student Teacher Relationship on Childrens Emotional Adjustment - Fadilla Ayuningtyas; Sofia Hartati; Tjipto Sumadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
The purpose of this study is to examine the impact of the academic press and student teacher relations on emotional adjustment in children aged 7-8 years. This study used a survey method with 132 respondents in East Jakarta, selected using stratified multistage cluster random sampling. Data collection uses three research instruments in the form of scales 1-3 which is adapted and developed from research indicators using student academic survey press with reliability values (α = .465), short version Student Teacher Relationship Scale (α = .599), and School Liking and Avoidance Questionnaire (α = .715). The results showed that 1) academic press did not had a direct negative effect on emotional adjustment, 2) teacher-student relations had a direct positive effect on emotional adjustment, and 3) academic press and teacher relations simultaneously had a positive effect on emotional adjustment which explained indirect effect of the academic press on emotional adjustment through student teacher relations as a mediator. This indirect influence illustrates that in a state of high positive relations, the academic press's role that the teacher seeks is understood by students as a way for teachers to improve achievement and emotional adjustment. In addition, the positive effect was increasing greater when academic press related together with the teacher-student relationship compared to the partial effect of student relations on emotional adjustment. This greater effect requires a ranking of the partial correlation of the teacher-student relation which is above or greater than the ranking of the partial academic press only.